2012
DOI: 10.1155/2012/734865
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction: Cytokine Profiles of Trophoblast Antigen-Stimulated Maternal Lymphocytes

Abstract: Intrauterine growth restriction (IUGR) is an important perinatal syndrome that poses several serious short- and long-term effects. We studied cytokine production by maternal peripheral blood lymphocytes stimulated by trophoblast antigens. 36 women with a diagnosis of IUGR and 22 healthy women with normal fetal growth were inducted. Peripheral blood mononuclear cells were stimulated with trophoblast antigens and levels of the proinflammatory cytokines IL-6, IL-8, IL-12, IL-23, IFNγ, and TNFα and the anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 56 publications
3
74
0
3
Order By: Relevance
“…However, the same study reported a relatively lower IFN-␥/IL-10 ratio from cells from women with IUGR and normal placental blood flow than from cells from those with normal pregnancy, as well as the production of lower levels of IL-13 from the cells of women in the IUGR group overall. Our own findings concerning the significantly altered profiles of IFN-␥ and IL-5 (a Th2=-type anti-inflammatory cytokine in the same family as IL-13) in association with SGA thus appear to be consistent with those of Raghupathy et al (33). Nevertheless, the particular functional relevance of these associations remains unclear.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the same study reported a relatively lower IFN-␥/IL-10 ratio from cells from women with IUGR and normal placental blood flow than from cells from those with normal pregnancy, as well as the production of lower levels of IL-13 from the cells of women in the IUGR group overall. Our own findings concerning the significantly altered profiles of IFN-␥ and IL-5 (a Th2=-type anti-inflammatory cytokine in the same family as IL-13) in association with SGA thus appear to be consistent with those of Raghupathy et al (33). Nevertheless, the particular functional relevance of these associations remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that deregulation of the immune system in early pregnancy is associated with adverse pregnancy outcomes, such as intrauterine growth retardation (IUGR), that can result in babies who are SGA (32). A generally stronger proinflammatory bias has been reported in a study of peripheral blood cells, tested at delivery, of women with babies with IUGR (33). However, the same study reported a relatively lower IFN-␥/IL-10 ratio from cells from women with IUGR and normal placental blood flow than from cells from those with normal pregnancy, as well as the production of lower levels of IL-13 from the cells of women in the IUGR group overall.…”
Section: Discussionmentioning
confidence: 99%
“…In patients suffering from implantation failure and recurrent pregnancy loss, the production of Th1 cytokines from isolated T-cells is increased relative to patients with normal pregnancies [44,45], our data from the CBA/CaH x DBA/2J confirms this. In addition, in the third trimester of pregnancy T-cells from patients with pregnancies complicated with IUGR express greater levels of IFN γ than those from normal pregnant controls [7]. We have shown that appropriate expression of p65 is essential for stimulation induced production of Th1 cytokines [13], suggesting that in these pregnancy pathologies ineffective alteration of p65 expression in maternal T-cells may underlie their progression.…”
Section: Discussionmentioning
confidence: 86%
“…The expansion of Tregs early in pregnancy is essential for protecting the early fetus from rejection since in the mouse depletion of Tregs prior to 10.5 days post coitus (dpc) results in fetal loss [5]. There is insurmountable evidence demonstrating the adverse effect of Th1 and Th17 responses in inducing both early pregnancy loss and intra uterine growth restriction (IUGR) in human and murine pregnancies, and conversely the beneficial effects of Th2 responses in pregnancy success [6,7]. Also clinically the remission of rheumatoid arthritis (RA) in pregnancy [8] is a direct effect of suppressed Th17 immunity since the cytokine IL-17, produced by Th17 cells, plays an essential role in the pathophysiology of rheumatoid arthritis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the normal group, FGR group with placental insufficiency showed a stronger pro-inflammatory bias that was characterized by enhanced levels of pro-inflammatory cytokines interleukin-8 (IL-8), interferon gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α), and decreased levels of anti-inflammatory cytokines IL-13 and IL-10. FGR group with placental insufficiency indicated a possible pro-inflammatory Th1-bias as seen from the elevated levels of IL-12, a Th1-inducing cytokine, than the FGR group without placental insufficiency (Raghupathy et al 2012). A murine FGR model induced by multiple injections of antiphospholipid antibodies (aPLs) and mediated by Fc γ-receptor, revealed augmented levels of TNF-α in maternal plasma, deficient interstitial EVT invasion, impaired spiral artery remodeling and elevated placental nitrosative stress.…”
Section: R230mentioning
confidence: 96%